A method for rapid estimation of residual stresses in metal samples produced by additive manufacturing (Fracture and Structural Integrity, 2024)
The mechanical methods for measuring residual stresses typically rely on so-called destructive techniques where some stress components can be determined based on part deflection after material removal (cutting, etching, drilling, etc.). While these methods don't provide a comprehensive representation of residual stresses within the entire part, they can be readily applied in most manufacturing labs. In this study, we propose an efficient method for determining residual stress within additively manufactured cylindrical samples of stainless steel. The method is based on the assumption of a relation between the axial component of residual stress (normal to cross-section) and the cylinder radius. The general form of this relation is proposed based on data from numerical simulations using linear, parabolic or piecewise approximations. The parameters for the proposed relation are defined using equilibrium equations for total force and moment. The proposed method relies on an experiment with a mechanical cut along the cylinder. Consequently, the deflection of the cylinder halves after the cut allows for obtaining the equivalent bending moment.
Keywords: additive manufacturing; residual stress; stainless steel; mechanics of materials; mechanical properties